Boards of Trade and Canadian Urban Development - Bloomfield, Elizabeth (Urban History Review / Revue d'histoire urbaine, 1983)
Boards of trade or chambers of commerce were formed in over 600 Canadian communities between the 1840s and 1950. The key role of these associations of businessmen has been demonstrated or suggested in many studies of particular urban centres. This paper offers a more general overview, summarizing the federal legislation and the patterns of incorporation across Canada and outlining the significance of boards of trade as city-building agencies.